Depression in cancer patients undergoing chemotherapy in a tertiary care hospital: a cross-sectional study - Vaidya, Shivani S.; Sharma, Sarita K. (International Journal Of Community Medicine And Public Health, 2019)
Background: Cancer is the second most common cause of death after heart diseases and it accounted for 8.8 million deaths worldwide in 2015. The long course of treatment, repeated hospitalisations, and the side effects of chemotherapy along with the trauma of being diagnosed with cancer has a significant effect on psyche of cancer patient. Depression is the most frequent cancer related symptom and 15-25% of cancer patients are affected by depression. The aim of this study is to determine the levels of depression in cancer patients undergoing chemotherapy. Methods: Present cross-sectional study was conducted amongst cancer patients undergoing chemotherapy at Day Care Centre, Department of Radiation Therapy and Oncology, Government Medical College and Hospital, Nagpur. 95 participants were interviewed using predesigned and pretested questionnaire based on the Beck’s Depression Inventory. Results: Among the study subjects, 70 (73.69%) had depression of which 15 (21.42%) had borderline clinical depression, 44 (62.85%) had moderate depression and 11 (15.73%) had severe depression. None of the study subjects had extreme depression. Conclusions: Majority of the study subjects receiving chemotherapy were depressed.